2018
DOI: 10.1177/2168479018768514
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Safety Information in the Investigator’s Brochure: Inconsistencies and Recommendations

Abstract: A survey was undertaken to gain an understanding of current industry practices in the preparation of the safety information for the Investigator's Brochure (IB). Sixteen of a potential 25 respondents completed a survey (64% response rate). Five respondents represented pharmaceutical and biotech companies, and 11 were consultants or worked at contract research organizations for such companies. The results showed a lack of uniformity of practices. This may be due to the lack of harmonized regulations and guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…When debating their involvement in the production of IBs, the majority of participants (61%) indicated that they preferred to locate the RSI as a separate section, Section 8, rather than as a subsection of Section 7. These results are in line with data from a previous web-based survey that was conducted to understand current industry practices in the preparation of safety information for the IB [16].…”
Section: Reference Safety Information In the Ibsupporting
confidence: 88%
See 1 more Smart Citation
“…When debating their involvement in the production of IBs, the majority of participants (61%) indicated that they preferred to locate the RSI as a separate section, Section 8, rather than as a subsection of Section 7. These results are in line with data from a previous web-based survey that was conducted to understand current industry practices in the preparation of safety information for the IB [16].…”
Section: Reference Safety Information In the Ibsupporting
confidence: 88%
“…Where necessary, the RSI section of the IB is to be updated annually after the Development Safety Update Report data-lock point by a substantial amendment. All other safety information comprising a detailed overview on the safety profile of the IMP should be provided in the subsection on the 'Effects in Humans' and in the 'Summary of Data and Guidance to the Investigator' (Section 7) [14,16].…”
Section: Reference Safety Information In the Ibmentioning
confidence: 99%
“…Klepper and Fontaine (2018) conducted a survey among individuals working in pharmaceutical and biotech companies or at contract research organizations that assess the compilation of safety information in IBs. The survey showed a lack of uniformity of practices that ''may be due to the lack of harmonized regulations and guidelines'' [15]. Recently, our research team published findings of a cross-sectional study investigating the reporting quality of preclinical efficacy studies compiled in IBs [16].…”
Section: What Are the Implications And What Should Change Now?mentioning
confidence: 99%
“…Ethics Committees should establish a safety management system to enable clinical trial investigators to conveniently and systematically manage SAEs and SUSARs on site. Investigators could then comprehensively analyze and evaluate the risks of subjects, produce a periodic risk evaluation report, and report to the Ethics Committee on a timely basis [6] .…”
Section: Suggestions On Countermeasuresmentioning
confidence: 99%
“…Reference safety information (RSI) in the investigators’ brochure is the main source of information regarding an unexpected SAE [6] . However, as regulated in GCP-2020, sponsors need only update the investigators’ brochure once a year during the clinical trial.…”
Section: Suggestions On Countermeasuresmentioning
confidence: 99%